2010
DOI: 10.1096/fj.09-151480
|View full text |Cite
|
Sign up to set email alerts
|

FOXO3a mediates signaling crosstalk that coordinates ubiquitin and atrogin‐1/MAFbx expression during glucocorticoid‐induced skeletal muscle atrophy

Abstract: Muscle atrophy is a consequence of chronic diseases (e.g., diabetes) and glucocorticoid-induced insulin resistance that results from enhanced activity of the ubiquitin-proteasome pathway. The PI3K/Akt pathway inhibits the FOXO-mediated transcription of the muscle-specific E3 ligase atrogin-1/MAFbx (AT-1), whereas the MEK/ERK pathway increases Sp1 activity and ubiquitin (UbC) expression. The observations raise a question about how the transcription of these atrogenes is synchronized in atrophic muscle. We teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
95
3
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(108 citation statements)
references
References 60 publications
5
95
3
3
Order By: Relevance
“…Because binding of SP1 to Fn14 promoter is increased in denervated skeletal muscle, it is possible that activation of ERK5 stimulates SP1 activity, leading to the increased expression of Fn14. Previous studies have demonstrated that SP1 also gets activated and plays an important role in muscle atrophy in response to dexamethasone treatment (49,50). SP1 binds to promoter region and augments gene expression of ubiquitin, leading to increased activation of ubiquitinproteasome system.…”
Section: Discussionmentioning
confidence: 99%
“…Because binding of SP1 to Fn14 promoter is increased in denervated skeletal muscle, it is possible that activation of ERK5 stimulates SP1 activity, leading to the increased expression of Fn14. Previous studies have demonstrated that SP1 also gets activated and plays an important role in muscle atrophy in response to dexamethasone treatment (49,50). SP1 binds to promoter region and augments gene expression of ubiquitin, leading to increased activation of ubiquitinproteasome system.…”
Section: Discussionmentioning
confidence: 99%
“…According to some researches for mammals, excessive glucocorticoids causing skeletal muscle atrophy in avian might be due to: (1) promoting proteolysis in muscle by stimulating the expression of proteins such as E3-ligases, atrogin-1, MuRF-1 (muscle ring finger 1), and the lysosomal enzyme cathepsin L in the ubiquitinproteolytic pathways (Auclair et al 1997;Hasselgren 1999;Marinovic et al 2002;Combaret et al 2005;Baehr et al 2010); (2) limiting the protein synthesis by inhibiting the transport of amino acids into the muscle and inhibiting the stimulatory action of insulin, IGF-I (insulin-like growth factor-I), and amino acids on the phosphorylation of eIF4E-binding protein 1 (4E-BP1) and the ribosomal protein S6 kinase 1 (S6K1) (Shah et al 2000a, b;Liu et al 2004;Schakman et al 2008b). In addition, the upregulation of myostatin and FOXO and the downregulation of IGF-I and myogenin might take part responsibility for the dexamethasone-induced skeletal muscle atrophy in chick according to some researches for mammals in vitro as well in vivo (Lang et al 2001;Ma et al 2001Ma et al , 2003Sandri et al 2004;Gilson et al 2007;Du et al 2007;Schakman et al 2008b;Zheng et al 2010). However, the ultrastructural results in our study showed that the diminishment in skeletal muscle size was not only attributed to the dwindlement of myofibrils but to the decreases of glycogen granules, lipids and other components in in-termyofibrillar and interfilamentary spaces.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced FoxO activity could also account for the decrease in ubiquitin mRNA, because we recently found that FoxO indirectly regulates ubiquitin transcription. 51 Interestingly, Akt also phosphorylates XIAP at Ser-87. 52 The modification prevents the ubiquitination and subsequent degradation of XIAP; therefore, XIAP could be creating a positive-feedback loop to maintain its protein level and promote muscle cell survival by increasing Akt signaling.…”
Section: Discussionmentioning
confidence: 99%